Prevalence of temporomandibular disorders and its association with malocclusion in children: A transversal study - Macrì, Monica; Murmura, Giovanna; Scarano, Antonio; Festa, Felice (Frontiers in Public Health, 2022)
This study investigated the prevalence of temporomandibular disorders (TMDs) in a sample of children and adolescents and evaluated the correlation with occlusal variables. TMD signs and symptoms were recorded in 411 subjects (age range 7–15 years), divided into two groups: 214 subjects treated in Chieti (Italy) CG group and 197 in Murcia (Spain) MG group. Once the Angle dental class was identified, it was recorded if there were signs and symptoms of temporomandibular disorders (TMDs) and occlusal interferences. The percentages of signs and symptoms were compared to determine the differences among the groups for TMDs, bruxism, joint sounds, deviation during the opening, reduced opening/lateral/protrusive movements, malocclusions, and myofascial pain. There is no statistically significant difference between the two groups (χ2 = 1.057, p > 0.05). Subjects with Angle Class I (37.37%), deep bite (43.43%), and increased overjet (41.41%) showed a higher prevalence of TMD symptoms.